Review on Cement Stabilization/Solidification of Municipal Solid Waste Incineration Fly Ash - Chengcheng Fan; Baomin Wang; Tingting Zhang (Advances in Materials Science and Engineering)
Municipal solid waste incineration (MSWI) fly ash must be treated properly prior to being disposed in the security landfill due to its serious pollution toxicity. Nowadays, lots of studies have demonstrated that cement-based stabilization/solidification could reduce the toxicity pollution effectively by encapsulating the heavy metals into cement matrix, which leads to greater capacity and weight. This paper compares and discusses the MSWI fly ash treatment with the mostly used matrix materials such as Portland cement, phosphate cement, aluminate cement, and alkaline activated cement. Moreover, immobilization mechanism introduced by the interaction between the MSWI fly ash and hydrated cement matrix materials, such as the physical cementing effect, adsorption, isomorphous replacement, and complex precipitation, was explored in depth. The paper also pointed out some reasonable development directions for cement-based stabilization/solidification technology to improve the effectiveness and application of cement-based stabilization/solidification technology.